Pour une sociologie pragmatiste de l’expérience publique - Louis Quéré; Cédric Terzi (Sociologies, 2015)
Working at the crossroads between pragmatist philosophy and ethnomethodology, the authors set out the outlines of a sociology of public experiment. They propose to observe the political organization of local government bodies by studying the questions they ask, the way these are problematised and the procedures put in place to solve them. Applying this empirical approach to the question of Switzerland’s role in the Second World War reveals how a problematic situation can create a polemical environment which is likely to inhibit conducting research and hamper organizing a public experiment. These observations provide the critical framework for advocating that analyses be carried out on those people in favour of inquiries; that is, extending the scope of what should be problematised.